Design of compliant mechanism-based variable camber morphing wing with nonlinear large deformation. (15th November 2019) - Zhang, Yaqing; Ge, Wenjie; Zhang, Ziang; Mo, Xiaojuan; Zhang, Yonghong
The morphing wing with large deformation can benefit its flight performance a lot in different conditions. In this study, a variable camber morphing wing with compliant leading and trailing edges is designed by large-displacement compliant mechanisms. The compliant mechanisms are carried out by a hyperelastic structure topology optimization, based on a nonlinear meshless method. A laminated leading-edge skin is designed to fit the curvature changing phenomenon of the leading edge during deformation. A morphing wing demonstrator was manufactured to testify its deformation capability. Comparing to other variable camber morphing wings, the proposal can realize larger deflection of leading and trailing edges. The designed morphing wing shows great improvement in aerodynamic performance and enough strength to resist aerodynamic and structural loadings.